Hydrogen production from catalytic steam co-gasification of waste tyre and palm kernel shell in pilot scale fluidized bed gasifier - Yusup, S. (Nova Science Publishers, Inc., 2013)
In order to recover energy and recycle waste materials, an experimental study was performed on utilization of waste materials in catalytic steam gasification system. In current research, an alternative method of hydrogen production is achieved by blending of palm kernel shell (PKS) with waste tyre as a promising energy resource. Experiments were carried out at 600-800°C with steam/feedstock ratio (S/F) of 2-4 (kg/kg) and waste tyre/PKS ratio of 0-0.3 (kg/kg). This paper reports the results obtained from series of experiments that have been performed, on a pilot plant to improve hydrogen production efficiency. The highest H2 and total syngas content of 66.15 vol and 83.8 vol was achieved respectively under condition of 800°C and 30 wt of waste tyre blended with PKS and S/F ratio of 4 (kg/kg). The results obtained confirmed that mixtures of PKS and waste tyre in catalytic steam fluidized bed system produced a fuel gas with a calorific value of 14.76 MJ/Nm3 which has the potential to be utilised in engines. © 2013 by Nova Science Publishers, Inc. All rights reserved.